Identification of the microRNA alterations in extracellular vesicles derived from human haemorrhoids. Issue 5 (9th January 2023) - Wang, Kaijing; Zhang, Yuanyuan; Ma, Xiaoxue; Ge, Xinyu; Deng, Yewei
Abstract : New Findings: What is the central question of this study? What are the morphological features and microRNA (miRNA) expression features of extracellular vesicles (EVs) from haemorrhoids (Hae‐EVs) and normal tissues? What are the potential functions of the differentially expressed (DE) miRNAs in Hae‐EVs? What is the main finding and its importance? We present, for the first time, the morphological features and miRNA profile of human Hae‐EVs. Four hundred and forty‐seven significant DE‐miRNAs were identified. Gene ontology and pathway analysis of the DE‐miRNAs indicated diverse roles of the Hae‐EVs through different pathways. Our findings provide EV‐based pathological features and the underlying mechanism of haemorrhoids. Abstract: Extracellular vesicles (EVs) play important roles in many pathophysiologies as cell‐to‐cell communication vehicles. However, the features and potential functions of the EVs in haemorrhoids remain unclear. Therefore, we performed microRNA (miRNA) microarray analysis in EVs derived from haemorrhoid tissue to identify the profile of miRNAs in these EVs and predict their potential functions. We obtained typical EVs from both haemorrhoid and control tissues. Microarray analysis identified 447 miRNAs with significant differential expresssion (DE): 245 upregulated and 202 downregulated. The top three upregulated miRNAs in haemorrhoid EVs (Hae‐EVs), namely miR‐6741‐3p, miR‐6834‐3p and miR‐4254, were detected by RT‐qPCR in both Hae‐EVs and haemorrhoid tissues. Interestingly, we found a different expression pattern in the haemorrhoid tissues from that in Hae‐EVs. The potential target genes of these DE‐miRNAs were predicted by the miRWalk and miRDB databases. Gene ontology (GO) analysis of the target genes showed that the DE‐miRNAs contributed mainly to protein kinase activity, transcriptional activity and ubiquitin‐protein function. KEGG search found that the DE‐miRNAs might regulate the MAPK and Ras signalling pathways. These findings revealed, for the first time, the miRNA profiles in Hae‐EVs and provided potential targets and pathways involved in the pathological process.